Effect of Hyperoxia on the Growth and Photosynthesis of Polar Sea Ice Microalgae - Andrew McMinn; Pankowski, A; Delfatti, T (2005)
Sea ice algal communities are naturally exposed to very high concentrations of dissolved oxygen, which are likely to lead to increasing stress levels and declines in productivity. To test this hypothesis, cultures of Fragilariopsis cylindrus (Grun?) Hasle, Pseudo-nitzschia sp., Fragilariopsis curta (Van Heurch), Porosira glacialis (Grunow), and Entomoneis kjellmannii (Cleve) from Antarctic sea ice and Nitzschia frigida from Arctic sea ice were exposed to elevated dissolved oxygen levels, and their growth, maximum quantum yield, relative maximum electron transport rate, and photosynthetic efficiency were measured. At oxygen concentrations equivalent to approximately four times air saturation (89% oxygen), the growth rate and maximum quantum yield were significantly reduced in all taxa. When the oxygen concentration was regularly allowed to drop, the effect on growth and quantum yield was reduced. At lower dissolved oxygen concentrations (52%), the declines in growth and quantum yield were reduced but were still mostly significantly different from the controls (21% oxygen). It is likely that the generation of excess active oxygen radicals in the presence of free oxygen is responsible for most of the decline in growth, maximum quantum yield, relative maximum electron transport rate, and photosynthetic efficiency in all species. Â© 2005 Phycological Society of America.